Footprint‐Free Human Induced Pluripotent Stem Cells From Articular Cartilage With Redifferentiation Capacity: A First Step Toward a Clinical‐Grade Cell Source. (6th March 2014) - Boreström, Cecilia; Simonsson, Stina; Enochson, Lars; Bigdeli, Narmin; Brantsing, Camilla; Ellerström, Catharina; Hyllner, Johan; Lindahl, Anders
Abstract : This study shows that chondrocytes from autologous chondrocyte implantation donors can be efficiently reprogrammed into induced pluripotent stem cells using a nonintegrating method based on mRNA delivery. Results suggest that RNA‐based technology eliminates the risk of genomic integrations or aberrations, an important step toward a clinical‐grade cell source for regenerative medicine such as treatment of cartilage defects and osteoarthritis. Abstract : Human induced pluripotent stem cells (iPSCs) are potential cell sources for regenerative medicine; however, clinical applications of iPSCs are restricted because of undesired genomic modifications associated with most reprogramming protocols. We show, for the first time, that chondrocytes from autologous chondrocyte implantation (ACI) donors can be efficiently reprogrammed into iPSCs using a nonintegrating method based on mRNA delivery, resulting in footprint‐free iPSCs (no genome‐sequence modifications), devoid of viral factors or remaining reprogramming molecules. The search for universal allogeneic cell sources for the ACI regenerative treatment has been difficult because making chondrocytes with high matrix‐forming capacity from pluripotent human embryonic stem cells has proven challenging and human mesenchymal stem cells have a predisposition to form hypertrophic cartilage and bone. We show that chondrocyte‐derived iPSCs can be redifferentiated in vitro into cartilage matrix‐producing cells better than fibroblast‐derived iPSCs and on par with the donor chondrocytes, suggesting the existence of a differentiation bias toward the somatic cell origin and making chondrocyte‐derived iPSCs a promising candidate universal cell source for ACI. Whole‐genome single nucleotide polymorphism array and karyotyping were used to verify the genomic integrity and stability of the established iPSC lines. Our results suggest that RNA‐based technology eliminates the risk of genomic integrations or aberrations, an important step toward a clinical‐grade cell source for regenerative medicine such as treatment of cartilage defects and osteoarthritis.